Faktor-Faktor yang Mempengaruhi Collaborative Governance dalam Pengelolaan Hutan Adat Tigo Luhah Kemantan di Kabupaten Kerinci Berdasarkan Theory of Constraint - Afzal Rahman; Nora Eka Putri; Rizki Syafril (Jurusan Ilmu Administrasi Negara, 2022)
Hutan Adat is one of the forest management schemes in the social forestry setting initiated by the government in 2016. The social forestry program is a form of forest sector management with local wisdom that includes the forest area around the community residence. The forest is managed by local community for their own welfare. The distribution of Hutan Adat in Indonesia is currently widespread, one of which is in Kerinci Regency, Jambi Province. As part of Hutan Adat that is incorporated in social forestry scheme, Hutan Adat Tigo Luhah Kemantan collaborates with the Jambi Provincial Forestry Service through the Regional Technical Implementation Unit of the Kerinci Production Forest Management Group Unit 1. However, in its management, there are factors that affect the Collaborative Governance process. So, this study aims to describe two things. First, it describes the inhibiting factors for collaboration internally. Second, it defines the inhibiting factor for collaboration from the external side. Qualitative descriptive is used as the research method of this study. This qualitative research is intended to understand the phenomenon of inhibiting the collaborative governance process in the management of Hutan Adat Tigo Luhah Kemantan, Kerinci. This research was conducted at Hutan Adat Tigo Luhah by using interview, observation, and documentation study techniques. The results showed that there were two internal factors that influenced the collaboration process, namely (1) inconsistent management of Kelompok Usaha Perhutanan Sosial (KUPS), and (2) inadequate human resources. In addition, there is also one factor that influences externally from outside the collaboration, namely market constraints.